Analysis and control co-design optimization of natural gas power plants with carbon capture and thermal energy storage - Vercellino, Roberto, author; Herber, Daniel R., advisor; Bandhauer, Todd M., advisor; Quinn, Jason C., committee member; Coburn, Timothy C., committee member (Colorado State University. Libraries, 2022)
In this work, an optimization model was constructed to help address important design and operation questions for a novel system combining natural gas power plants (NGCC) with carbon capture (CC) and hot and cold thermal energy storage (TES) units. The conceptualization of this system is motivated by the expected evolution of the electricity markets towards a carbon-neutral electricity grid heavily penetrated by renewable energy sources, resulting in highly variable electricity prices and demand. In this context, there will be an opportunity for clean, flexible, and cheap fossil fuel-based generators, such as NGCC plants with CC, to complement renewable generation. However, while recent work has demonstrated that high CO2 rates are achievable, challenges due to high capital costs, flexibility limitations, and the parasitic load imposed by CC systems onto NGCC power plants have so far prevented its commercialization. Coupling TES units with CC and NGCC would allow to store thermal energy into the TES units when the electricity prices are low, either by subtracting it from the NGCC or by extracting it from the grid, and to discharge thermal power at peak prices, from the hot storage (HS) to offset the parasitic load of the CC system and from the cold storage (CS) for chilling the inlet of the NGCC combustion turbine and increase the output of the cycle beyond nominal value. For the early-stage engineering studies investigating the feasibility of this novel system, a control co-design (CCD) approach is taken where key plant sizing decisions (including storage capacities and energy transfer rates) and operational control (e.g., when to store and use thermal energy and operate the power plant) are considered in an integrated manner using a simultaneous CCD strategy. The optimal design, as well as the operation of the system, are determined for an entire year (either all-at-once or through a moving prediction horizons strategy) in a large, sparse linear optimization problem. The results demonstrate both the need for optimal operation to enable a fair economic assessment of the proposed system as well as optimal sizing decisions due to sensitivity to a variety of scenarios, including different market conditions, site locations, and technology options. After detailed analysis, the technology shows remarkable promise in that it outperforms NGCC power plants with state-of-the-art CC systems in many of the scenarios evaluated. The best overall TES technology solution relies on cheap excess grid electricity from renewable sources to charge the TES units -- the HS via resistive heating and the CS through an ammonia-based vapor compression cycle. Future enhancements to the optimization model are also discussed, which include additional degrees of freedom to the CC system, adapting the model to evaluate other energy sources and storage technologies, and considering uncertainty in the market signals directly in the optimization model.
Keywords: control co-design; natural gas; power plant; energy storage; carbon capture; optimization